ELEMENTS OF THE MUSICAL DISCOURSE IN “FUM (SMOKE)” BY DOINA ROTARU - Şerban MARCU (Studia Universitatis Babeş-Bolyai. Musica)
The present study is an analysis of the work entitled Fum (Smoke), for clarinet solo, written by the Romanian composer Doina Rotaru in 1996 and dedicated to the clarinetist Emil Vişenescu. The study enhances the author’s preference for ancient musical archetypes, such as the aulodic timbral archetype, the archetype of suspended time, the archetype of the ornament or that of the glissando. We also highlight the articulation of musical discourse in relation to symbolic structural principles: circular or spiral shapes, sacred numbers. The structural analysis also emphasizes the continuous variation process, starting from a generative motive which includes almost all elements of language the work is based on: Rubato rhythm, chromaticism, Enescu’s “x” cell, glissando and appoggiatura.